Comparative Analysis of Prediction Results of Decision Support Systems Simple Additive Weighting Method with Preference Selection Index in Determining Scholarship Recipients - Medi Hermanto Tinambunan; Djubir R.E. Kembuan; Vivi Peggie Rantung; Alfiansyah Hasibuan (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Educational Assistance needs to be a concern because currently the majority of students have the potential and ability but are constrained financially so this needs to be taken seriously by the government, currently, the government through the Ministry of Education has been trying to provide financial assistance in the form of scholarships including achievement improvement scholarships academic. Currently, to get a scholarship, each university certainly gets a limited quota. This is done to provide equal distribution of educational assistance, due to the large difference between the quota obtained and students who need assistance, so it is necessary to provide eligibility selection for students who are entitled to get scholarships. This study took sample data from the 2023 even semester scholarship list at Manado State University, especially in the Informatics Engineering Study Program, then normalized the data to use the SAW and PSI methods. After normalization, calculations were carried out using the SAW and PSI methods. predictions from the two methods will then be tested for the level of accuracy using the confusion matrix method. The result is that the SAW method has an accuracy rate of 98.13% and then the PSI accuracy rate is 97.24% based on the results of the prediction accuracy, the SAW method has a higher accuracy rate than PSI.